1999
DOI: 10.1093/emboj/18.5.1309
|View full text |Cite
|
Sign up to set email alerts
|

The JAK-binding protein JAB inhibits Janus tyrosine kinase activity through binding in the activation loop

Abstract: The Janus family of protein tyrosine kinases (JAKs) regulate cellular processes involved in cell growth, differentiation and transformation through their association with cytokine receptors. However, compared with other kinases, little is known about cellular regulators of the JAKs. We have recently identified a JAKbinding protein (JAB) that inhibits JAK signaling in cells. In the studies presented here we demonstrate that JAB specifically binds to the tyrosine residue (Y1007) in the activation loop of JAK2, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
626
3
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(656 citation statements)
references
References 41 publications
22
626
3
5
Order By: Relevance
“…4C). This is in agreement with the established inhibitory mechanism of SOCS-1 through direct binding to the kinases of the Janus family (23,24,53) and emphasizes the difference in the inhibitory mechanisms of SOCS-1 and SOCS-3.…”
Section: Discussionsupporting
confidence: 91%
“…4C). This is in agreement with the established inhibitory mechanism of SOCS-1 through direct binding to the kinases of the Janus family (23,24,53) and emphasizes the difference in the inhibitory mechanisms of SOCS-1 and SOCS-3.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, TEL-JAK2 transformed Ba/F3 cells expressing SOCS-1 died within 48 h as seen by staining with the vital dye 7-AAD and AnnexinV (Figure 2c). SOCS-1 binds to JAK2 through its SH2 domain and a peptide sequence that includes the phosphorylated Y1007 residue in the activation loop of JAK2 catalytic domain (Yasukawa et al, 1999). A point mutation at residue R105 in the SOCS-1 SH2 domain has been shown to impair SOCS-1 mediated inhibition of JAK kinases .…”
Section: Socs-1 Inhibits the Proliferation Of Cells Transformed By Onmentioning
confidence: 99%
“…SOCS-1 binds directly to the conserved regulatory tyrosine in the activation loop of the JAK2 kinase (JH1) domain through its SH2 domain and inhibits JAK kinase activity presumably through occlusion of the substrate binding site Yasukawa et al, 1999). SOCS-1 also interferes with signaling through the KIT receptor tyrosine kinase, though in a manner which does not suppress its catalytic activity (De Sepulveda et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SOCS suppress cytokine signal transduction by binding to phosphorylated tyrosine residues on cytokine receptor chains and the receptor-associated tyrosine phosphorylated Jaks via the SH2 domain. The binding results in switching off Jaks by acting pseudosubstrates and recruiting ubiquitination machinery via the SOCS-box domain (Yasukawa et al, 1999). SOCS1 is induced by various cytokines including interferon (IFN)-g, interleukin-4, TNF-a, as well as growth hormones, and downregulates the signals induced by these cytokines in a feedback loop.…”
Section: Introductionmentioning
confidence: 99%